Application of Video Analysis for Enhancing Kinematic Parameters and Techniques of Yoga Performers (Indian Journal of Public Health Research & Development, 2021)
Background: Yoga asanas help to increase the wholesome development of an individual. At the same time,the execution of the asanas gives complete benefits to the practitioners.Aim: The purpose of the study was to find out the application of video analysis for enhancing kinematicparameters and techniques of yoga performers.Methods and Material: For this study, three men yoga performers selected from SRMV Maruthi Collegeof Physical Education, Coimbatore, Tamil Nadu, India. The age of the participants was 24 years. He hada good experience in performing yoga including difficult classical asanas. For this study angle of joints,movement of body parts and position of balance, holding time were selected as dependent variables. SportsInsight motion analysis cameras and software were used to find out the angle of joints, movement of bodyparts and body balance. The baseline kinematic variables were tested before intervention. At the time ofintervention, the execution of the asana (virksasana) was recorded by the researcher through the sportsmotion analysis camera and software.Statistical analysis used: Descriptive statistics were used to analyse the performance of the yoga performers.Results: The captured video was showed to the participant to understand his execution of asana. Theresearcher gave the necessary guidance to correct the mistakes and provide opportunities for self-evaluation.After the 10 days of training, post-test was conducted and data were collected from the participant.Conclusion: It is concluded that the application of video analysis produced a significant difference inangle of joints, movement of body parts among the yoga performers. It is concluded that the application ofvideo analysis produced significant improvement in the position of balance, holding time among the yogaperformers.
Keywords: video analysis, kinematic parameters, techniques, asanas, virksasana. the angle of joints, movement of body parts and position of balance, holding time, sports motion analysis camera and software.